An odd couple: Domestic crimes an international responsibility in the Special Tribunal for Lebanon - Milanović, Marko (Journal of international criminal justice, 2007)
This article examines one of the most serious flaws of the Statute of the Special Tribunal for Lebanon (STL): while it provides that Lebanese domestic law is the sole source of crimes over which the STL will have jurisdiction, it at the same time applies to these domestic crimes uniquely international forms of criminal responsibility, namely joint criminal enterprise and command responsibility. By doing so, the Statute is in violation of the nullum crime sine lege principle, since it would allow for the conviction of persons who could not be held responsible under Lebanese law. The purpose of this article is to highlight some ways out of this problem